How do University Professors build High Resilience? Case Studies - Sierra-Molina, Teresa de Jesús; Sevilla-Santo, Dora Esperanza (Revista Electrónica Educare, 2021)
Introduction. Resilience is understood under a triadic perspective as the creation of new strategies from the need to resist in the interaction of personal characteristics, with a stable family environment and a supportive context. Objective. To know how university teachers build their high resilience so that they and higher education institutions (HEI) can reduce risk factors and promote mechanisms allowing high levels of resilience and greater time working as teachers. Methodology. A qualitative approach of descriptive scope for eight professors of engineering and psychology of public and private HEI from the Mexican southeast who were part of a doctoral work project with a mixed approach. Results. First, the importance of professional aspects and the teaching work in building high resilience is identified since these two elements act as protective and risk factors, both internal and external, that allow maintaining resilience. Second, next in importance are personal aspects that function as protectors and risk factors, such as combining teaching with the motherhood of young children. Third, institutional aspects are identified, which are perceived, almost equally, as protective and risky. Finally, social aspects are more perceived by the engineering teaching personnel and the full-time working staff. Conclusions. The dynamics and bidirectionality of these aspects to build higher resilience levels are corroborated; according to the experiences of the teaching staff, these aspects are perceived as protective factors that mitigate many risks in the form of challenges that current teaching poses to teachers.